Defect mechanisms in BaTiO3‐BiMO3 ceramics. Issue 6 (8th January 2018) - Kumar, Nitish; Patterson, Eric A.; Frömling, Till; Gorzkowski, Edward P.; Eschbach, Peter; Love, Ian; Müller, Michael P.; De Souza, Roger A.; Tucker, Julie; Reese, Steven R.; Cann, David P.
Abstract: Often, addition of Bi M O3 to BaTiO3 (BT) leads to improvement in resistivity with a simultaneous shift to n‐type conduction from p‐type for BT. In considering one specific Bi M O3 composition, that is, Bi(Zn1/2 Ti1/2 )O3 (BZT), several prospective candidates for the origin of this n‐type behavior in BT‐BZT were studied—loss of volatile cations, oxygen vacancies, bismuth present in multiple valence states and precipitation of secondary phases. Combined x‐ray and neutron diffraction, prompt gamma neutron activation analysis and electron energy loss spectroscopy suggested much higher oxygen vacancy concentration in BT‐BZT ceramics (>4%) as compared to BT alone. X‐ray photoelectron spectroscopy and x‐ray absorption spectroscopy did not suggest the presence of bismuth in multiple valence states. At the same time, using transmission electron microscopy, some minor secondary phases were observed, whose compositions were such that they could result in effective donor doping in BT‐BZT ceramics. Using experimentally determined thermodynamic parameters for BT and slopes of Kröger‐Vink plots, it has been suggested that an ionic compensation mechanism is prevalent in these ceramics instead of electronic compensation. These ionic defects have an effect of shifting the conductivity minimum in the Kröger‐Vink plots to higher oxygen partial pressure values in BT‐BZT ceramics as compared to BT, resulting in a significantly higher resistivity values in air atmosphere and n‐type behavior. This provides an important tool to tailor transport properties and defects in BT‐Bi M O3 ceramics, to make them better suited for dielectric or other applications.